Eichhornia crassipes Efficacy in Secondary Wastewater Treatment in the Western Highlands of Cameroon - Amandine Elodie Manekeu Tanetsa; Martin Lekeufack; Marcelle Léonce Edzigui Tsimi; Gabriel Nicodème Tsetagho; Raoul Carmel Longniang; Théophile Fonkou (The Scientific World Journal)
Wastewater treatment using lagoons technology is recognised to have potential to protect the environment and preserve water resources. The implementation requires mastery of ecological conditions of operation and management of the plants used. We aimed to contribute to the implementation of macrophyte-based lagoons for wastewater treatment in the Western Highlands of Cameroon. We used two sets of four lagoons in series; one was vegetated with E. crassipes, while the other served as the control. Each set constituted an anaerobic, two facultative, and maturation lagoons. Each lagoon system was supplied with primary-treated domestic wastewater from the wastewater treatment plant of the University of Dschang, Cameroon, at a hydraulic loading rate of 1.13 m3/day. Monthly wastewater samples were collected from the inflow and outflow of each lagoon for physicochemical and bacteriological analyses, and plant growth was assessed biweekly for six months spanning the dry and rainy seasons. Macrophyte lagoons showed positive plant growth during both seasons. The highest plant height (10.67 and 25.21 cm), longer roots (11.3 and 37.41 cm), and the highest number of new buds (14 and 20 buds) were obtained during the dry and rainy seasons, respectively. Plants were significantly (P < 0.0001) taller in facultative lagoons in the rainy season than in the dry season. Vegetated lagoons significantly (P < 0.05) contributed to reducing TSS (−08.36% and 82.25%), true color (44.46% and 82.31%), orthophosphates (63.1% and 86.59%), and BOD5 (−56.79% and 56.06%) during the dry and rainy seasons, respectively. 100% elimination of fecal streptococci (FS) and 74.89% and 43.80% of fecal coliforms (FC) were observed in the dry and rainy seasons, respectively. Significant (P = 0.0019) FS elimination was more in the dry season than in the rainy season. However, the average residual content of FC (190,000 UFC/100 ml) was still higher than WHO limits (≤1000 UFC/100 ml) for nonrestrictive reuse in agriculture. E. crassipes can be efficiently used in lagoon systems for domestic wastewater treatment in the Western Highlands of Cameroon.